ANALISIS KEPUASAN MAHASISWA TERHADAP KUALITAS LAYANAN PENDIDIKAN DI STAIN PADANGSIDIMPUAN - Asnah, Asnah (Institut Agama Islam Negeri Padangsidimpuan, 2014)
AbstractThis research was aims to determine the level of student satisfaction with services at STAIN Padangsidimpuan education, the quality of service provided by the staff and faculty, as well as the strengths and weaknesses of educational services in Padangsidimpuan STAIN. The method used in this research is descriptive method with quantitative and qualitative approaches. A total of 250 students were used as a sample by using three sampling techniques, namely stratified cluster random sampling. Data collected through questionnaires and intervieu. Furthermore, the data were analyzed using inferential statistical analysis with the formula Importance Performance Analysis. From the analysis it is known that the level of student satisfaction with services at STAIN Padangsidimpuan education has reached a category that is equal to 69.72% satisfied. Overall, the quality of service at STAIN Padangsidimpuan is